2012
DOI: 10.2478/v10220-012-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Humic-Fatty Acid Preparation on Production Parameters and Meat Quality of Growing Rabbits

Abstract: The Effect of Humic-Fatty Acid Preparation on Production Parameters and Meat Quality of Growing RabbitsThe aim of the study was to determine the effect of a humic-fatty acid preparation on production parameters and meat quality of rabbits. Three groups of New Zealand White rabbits were used (one control and two experimental) with 8 animals per group. The animals of group C (control) were fed standard pelleted diet, group H5 received a control diet supplemented with 5%, and group H10 a control diet with 10% hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…Ozturk et al (2012) found that broilers fed these substances show lighter and darker thigh and breast meat, respectively, with a pH value and a water-holding capacity that varied according to the supplementation level. In the present work, the meat pH at 24 h (pH24) was found to be between 5.68 and 5.71, which is slightly higher than that observed by Miśta et al (2012) in New Zealand White rabbits fed diets containing 5-10 % humic-fatty acid preparations. These authors reported a greater effect on pH24 of the 10% humic-fatty acid preparation.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Ozturk et al (2012) found that broilers fed these substances show lighter and darker thigh and breast meat, respectively, with a pH value and a water-holding capacity that varied according to the supplementation level. In the present work, the meat pH at 24 h (pH24) was found to be between 5.68 and 5.71, which is slightly higher than that observed by Miśta et al (2012) in New Zealand White rabbits fed diets containing 5-10 % humic-fatty acid preparations. These authors reported a greater effect on pH24 of the 10% humic-fatty acid preparation.…”
Section: Discussioncontrasting
confidence: 67%
“…feed conversion). Research by Miśta (2007) and Miśta et al (2012) has shown that, by acting on intestinal mucosa and on microflora stabilization, the HUSs used as feed additives for rabbits may improve nutrient utilization. Apart from the dose, it appears difficult to compare the effects of SBOs sourced from residual vegetable matter and HUSs obtained from different soil sites and preparations, and tested on different species and under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our experiment are coherent with the results obtained by other scientists. Mista et al (2012) studied the effect of preparation of humic-fatty acids (HFA) on productive indicators and quality of meat of fattening rabbits. Composition of HFA was 80% of humic-mineral constituents (silicon, aluminium, iron, calcium, sodium, magnesium, phosphorus, manganese, zinc, cuprum, potassium, cobalt, selenium) and 20% of plant oils (oleic, linoleic, palmic acids).…”
Section: Discussionmentioning
confidence: 99%
“…Scientists all around the globe seek for, study and develop efficient mineral additives, preparations and biologically active substances for treatment of impaired metabolism in animals, including rabbits (Raafat, 2011;Mista & Rzasa, 2012;Elokil et al, 2019;Lieshchova et al, 2020). According to most scientists, the most effective way of preventing metabolic disorders in rabbits is use of complex preparations, and therefore the search for them still continues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation